2008
DOI: 10.2141/jpsa.45.20
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Citric Acid and Microbial Phytase Supplementation on Performance and Phytate Phosphorus Utilization in Broiler Chicks

Abstract: An experiment was conducted to investigate the e ects of supplementation of broilers diet with both citric acid and microbial phytase on performance criteria and utilization of phytate phosphorus (P) in broiler chicks from day old to d of age. The experiment was carried out using a completely randomized design with factorial arrangement of (,. and percentage of citric acid and and IU of phytase enzyme per kg). Experimental diets were formulated so that had. lower available P than positive control diet. Four re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
16
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 17 publications
7
16
0
Order By: Relevance
“…The reason for not seeing significant effect on FCR in our findings was probably due to both increase in BWG and FI simultaneously. This result is in agreement with some studies (Ebrahimnezhad et al, 2008;Nourmohammadi et al, 2010). Ferguson et al (1998);Preston et al (2000) and Hassanabadi et al (2007) reported that adding different levels of phytase (500 and 1000 IU kg −1 ) caused a tendency to increase carcass yield.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The reason for not seeing significant effect on FCR in our findings was probably due to both increase in BWG and FI simultaneously. This result is in agreement with some studies (Ebrahimnezhad et al, 2008;Nourmohammadi et al, 2010). Ferguson et al (1998);Preston et al (2000) and Hassanabadi et al (2007) reported that adding different levels of phytase (500 and 1000 IU kg −1 ) caused a tendency to increase carcass yield.…”
Section: Discussionsupporting
confidence: 93%
“…With the same purpose, researchers (Viola and Vieira, 2007) have reported the beneficial effects of organic acids such as CA as alternatives to some feed additives and antibiotics on performance and carcass quality of broilers. Similar results with present study were found by Ebrahimnezhad et al (2008) and Nourmohammadi et al (2010) indicating that addition of CA caused significant increase in carcass yield of broiler chickens. Ebrahimnezhad et al (2008) and Nourmohammadi et al (2010) found that dietary CA and phytase supplementation had affected the relative weight of liver, abdominal fat pad and heart weight of broiler chickens at 42 d. On the other hand, Abdel-Azeem et al (2000) noted that addition of CA to the diet was associated with higher and lower dressing and liver percentages, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…ALP is a metalloenzyme known to have an important role in bone mineralization and to be affected by dietary Zn. Studies conducted with chicks had reported that a decrease in the dietary P level produces increased ALP activity (Brenes et al, 2003;Ebrahimnezhad et al, 2008;Nourmohammadi et al, 2010). In these studies, dietary CA supplementation facilitated the liberation of phytate P and increased the plasma P concentration, decreasing ALP activity, as also observed in the present study (Table 4).…”
Section: Discussionsupporting
confidence: 86%